A EuIII‐MOF with Bis(2‐carboxyethyl)isocyanurate for Luminescence Sensing of Fe3+ and SCN– Ions. Issue 17 (21st August 2017) - Zhang, Yanan; Zhang, Peng; Yin, Haiju; Cheng, Jing; Kang, Yifan
Abstract : The water‐stable 3D lanthanide‐organic framework ( Ln ‐MOF) [Eu(bci)(H2 O)]· 2H2 O n (1 ) [H2 bci = bis(2‐carboxyethyl)isocyanurate] was synthesized under hydrothermal conditions. Compound1 ‐Eu exhibits a 3D open‐framework connected by Eu–(μ‐O)2 –Eu chains and bci ligands. Meanwhile, 1 ‐Eu exhibits highly efficient luminescent sensing for environmentally relevant Fe 3+ and SCN – ions through luminescence quenching. These results indicated that it could be utilized as a multi‐responsive luminescence sensor. Abstract :